THE RELATIONSHIP BETWEEN MENTAL WORKLOAD WITH WORK STRESS ON HOSPITAL NURSES - Mella Anyndya Hernata; Merry Tiyas Anggraini; M. Riza Setiawan (Universitas Muhammadiyah Semarang, 2017)
During their work, nurses have a mental overload. A nurse should have good communication to care the patient who has differentiated behavior and health condition. A bad communication between nurse and patient result in work stress to the nurse that potential lead to human error. This study aims to know the correlation between mental workload and work stress on hospital nurses. This study was an analytical observational study with a cross sectional approach, data was obtained in October-November 2016. The instruments used NASA-TLX questionnaire to measure mental workload and HRV uBioClip v70 to measure stress. Data was analyzed by Fisher‟s-Exact correlation test both univariately and bivariately. A total sample of 32 nurses who worked in hospital of Muhammadiyah Gubug. Bivariate analysis showed that from 14 nurses who had under load-optimal load, 8 (57,1%) of them are suffered to work stress.Whereas from 14 nurses who had over load, all of them (100%) are suffered to job stress. Statistical analysis showed a correlation between mental workload and job stress in nurses at hospital of Muhammadiyah Gubug (p=0,003). The results proved that mental workload has a significant correlation with job stress. Key words: Mental workload, work stress, nurse